Value, rent, and nature: The centrality of class. Issue 1 (March 2020) - Greco, Elisa; Apostolopoulou, Elia
Welcoming the renewed interest in value among geographers, we engage with the arguments that Kay and Kenney-Lazar (2017) put forward in their article, 'Value in Capitalist Natures: An Emerging Framework'. We organize our contribution around three important aspects that can advance current debates and propose an agenda for future research. Firstly, we argue that current debates need to refocus from whether nature contributes to material wealth to whether and how nature relates to the value form under capitalism. Secondly, we highlight the need for a systematically joint analysis of value and rent to understand the role of nature in capitalism. This analysis leads to a focus on class and class struggle and requires interdisciplinary collaborations between nature–society geographers and other scholars working within the value theoretical framework to bridge current struggles over rent and value. Thirdly, contra Kay and Kenney-Lazar, we argue that beyond capitalism we do not need either alternative valuation systems or value but rather a new vocabulary to redefine social needs and social wealth.